HIV-1 matrix protein p17: a key factor in HIV-associated cancers - Zhang, Yuxin; Li, Mengzhu; Lin, Fangyu; Guo, Rui; Wu, Danhui; Shen, Rui; Harypursat, Vijay; Chen, Yaokai; Chen, Yemiao (Frontiers in Virology, 2025)
In the present era of highly active antiretroviral therapy (HAART), as a consequence of long-term antiretroviral medication consumption, extended patient survival, and persistent immune activation, people who live with HIV (PLWH) have become more susceptible to chronic diseases such as tumors, cardiovascular diseases, and diabetes mellitus when compared to the general population. Although the HIV-1 matrix protein p17 (p17) was initially thought to be a structural protein of HIV-1, recent studies have revealed its close association with elevated incidence of tumors, particularly lymphomas, in HIV-1-infected individuals. Experimental results indicate that p17 may promote the proliferation and clonogenicity of various cell types. Moreover, p17 and its variants are directly and indirectly linked to the occurrence and development of lymphomas. The sustained detection of p17 in clinical specimens—particularly lymph node biopsies and plasma samples from HIV/AIDS patients—points to its possible involvement in tumor microenvironment modulation. Here, we present a brief overview of the roles played by p17 in the regulation of cellular functions, promotion of lymphoma occurrence, and formation of the tumor microenvironment, as well as the potential molecular mechanisms which are fundamental to the functionality of p17. Additionally, we briefly outline other HIV-related tumors that p17 may likely be involved in. Investigation of p17 mechanisms and their interactions with oncogenic pathways is essential for understanding HIV-associated tumorigenesis. These findings may facilitate the development of novel therapeutic strategies for HIV-related malignancies